Phylogenetic, antagonist potential, biochemical profile and expression of NBS-LRR resistance gene candidates of Colletotrichum gloeosporioides on peanut seeds (Arachcis hypogaea L. cv. Margenta) - Rajeendran, Allegendran (2017)
Peanuts (Arachis hypogaeaL. cv. Margenta) are important as a crop with high content of protein and oil in seeds. At present in Malaysia, the practices for control of pathogenic fungi rely mainly on how the pesticides are applied. This resulted in some of the serious hazards on human health especially the farm workers and consumer. Due to the over use of pesticides to control the growth of pathogenic fungi, some of the strains have developed increased resistance against these chemicals. Various approaches which had been carried out to control plant diseases. Besides, the biological control of plant diseases is feasible and environment-friendly as opposed to chemicals and pesticides which causes environmental pollution. The first objective of the study is to determine the phylogenetic relationship of Colletotrichum gloeosporioides from infected peanut seeds.The cultivars of peanuts (Margenta) were found to be susceptible to fungal diseases caused by the pathogens C. gloeosporioides. The fungus Colletotrichum gloeosporioideswas isolated from naturally infected plants and the molecular identification of the species level was done using amplification via ITS1 and 4 primer with sequencing and a phylogenetic tree by MEGA 7. The phylogenetic tree confirmed that the ITS region was an isolated from of peanut fungus closely related to C. gloeosporioides. The potential biological disease decreasing ability of antagonistic mycorrhizal fungi: Trichoderma virens, Trichoderma asperellum, Trichoderma harzanium, Hypogea virens and Trichoderma begomovirus to manage seed diseases and root rot of groundnut plants also studied. The antagonistic abilityof T. virens, T. asperellum, T. harzanium, H. virens and T. begomovirus was screened in vitro by the dual culture technique. Trichoderma harzanium strongly inhibited the fungal growth of C. gloeosporioides by 80.6%, followed by T. virens (78.4%), T. asperellum(65.3%), T. begomovirus (62.2%) and H. virens (48.3%). Two fungal biocontrol agents (BCAs), T. virens and T. harzianum were found to strongly inhibit the growth of Colletotrichum sp. through mycoparasitism, competition and antibiosis. The highest chitinase enzyme activity was recorded with T. harzanium (5.51 IU/mL), followed by T. virens (4.2 IU/mL), T. asperllum(2.32 IU/mL), T. begomovirens (0.54 IU/mL ), and H. virens (0.12 IU/mL). The highest β-1,3-glucanase enzyme activity was recorded with T. virens(34.4 IU/mL), followed by H.virens (34.4 IU/mL), T. begomovirens (25.3 IU/mL ), T. harzianum (7.6 IU/mL), and T. asperllum (4.8 IU/mL). The effects of C. gloeosporioides on its morphology, germination and fatty acid profile in regards to the quality of peanut seeds aslo conducted. C. gloeosporioides infection had a significant effect on the changes of the physical structure of seeds based on seed volume. The 50-seed volume was found to be significantly lower (10.2 mL) in C. gloeosporioides infected seeds than that of uninoculated seeds (11.4mL). Germination of inoculated seed significantly reduced (65.0%) compared to un-inoculated seeds (control).The protein content of inoculated seeds was found to be significantly higher (40.6%) compared to un-inoculated seeds (38.5%). However, the oil content is similar between inoculated and un-inoculated seeds. A fatty acid profile determination was done by Gas Chromatography, and the percentage of fatty acids was analysed. The saturated fatty acids were increased while the unsaturated fatty acids decreased due to an oxidation process, and consequently there was a production of toxic metabolites in the seeds which also reduced the germination percentage. In this study, genes related to the plant defense system had been isolated by using PCR, and analyses of resistant gene candidates (RGCs) in specific host-pathogen intractions was carried out. A pair of degenerate oligonucleotide primers designed from conserved motifs of P-loop and GLPL regions, common to many resistance genes, were used to amplify the Nucleotide-Triphosphate Binding Site (NBS) regions of RGAs from the Fabaceae species. A total of three partial RGAs fragments designated as AhRGC 1, AhRGC 2 and AhRGC 3 were amplified from Arachis hypogaea. Therefore, the application of biocontrol is alternative to fungicides and environmentally friendly strategy to control seed-borne pathogens. There is a generation of complimentary environment for BCAs as biopriming due to initial moisture content inside the seed, equal chance to obtain nutrient sources from exudates of seed which can contribute to proliferate rapidly at the surface of a seed for their potential of being a biocontrol. As a conclusion, the T. virens and T. harzianum have the potential to control C. gloeosporioides on peanut seeds.